Características del maltrato hacia estudiantes de medicina de una universidad pública del Perú - Munayco Guillén, Fernando (2016)
Objectives. To determine the characteristics of mistreatment among medical students at a public university in the province Ica, Peru. Materials and methods. This cross-sectional study was performed in 2012, and used a probability sample of medical students (freshman to sixth year) at the Universidad Nacional San Luis Gonzaga. A 23-item survey with a Likert scale was used to measure the students' perceptions of psychological, physical, academic and sexual mistreatment. Univariate and bivariate statistical analysis were performed. Results. A total of 281 students were surveyed. The perception of psychological mistreatment was 96.8%; academic, 86.8%; physical, 62.6% and sexual, 20.6%. Physical abuse increased during the clinical-surgical study cicle (p = 0.001). Medical doctors and residents were the main aggressors. Male students reported of receiving assignments as a punishment, not receiving credits for their work, physical mistreatment, verbal threats, insults, or being teased because of their etnic background. Female students were more likely to have experienced sexual abuse. Report of sexual abuse frequently ocurred at the university (45.3%, p=0.002) and hospital (45.0%, p=0.046). Women frequently reported not knowing to whom or where to denounce the abuse (54.6%, p=0.042) and not reporting it because it stopped (56.9%, p=0.048). Conclusions. There is a high prevalence of abuse among students in which their characteristics as sex, level of study and aggressor allow to identify the types of abuse that they receive.